Recent Publications upon Economics (Quarterly Journal of Economics, 1897)
Journal Article Recent Publications upon Economics Get access The Quarterly Journal of Economics, Volume 11, Issue 3, April 1897, Pages 327–334, https://doi.org/10.1093/qje/11.3.327 Published: 01 April 1897